1988
DOI: 10.1212/wnl.38.8.1285
|View full text |Cite
|
Sign up to set email alerts
|

Reactive microglia are positive for HLA‐DR in the substantia nigra of Parkinson's and Alzheimer's disease brains

Abstract: We detected large numbers of HLA-DR-positive reactive microglia (macrophages), along with Lewy bodies and free melanin, in the substantia nigra of all cases studied with Parkinson's disease (5) and parkinsonism with dementia (PD) (5). We found similar, but less extensive, pathology in the substantia nigra of six of nine cases of dementia of the Alzheimer type (DAT) but in only one of 11 age-matched nonneurologic cases. All dementia cases with a premortem diagnosis of DAT or PD showed large numbers of HLA-DR-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

42
1,776
2
20

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,584 publications
(1,883 citation statements)
references
References 0 publications
42
1,776
2
20
Order By: Relevance
“…Thus in PD itself, α‐synuclein itself might be an antigen used by MHC II during antigen presentation and thus leading to the observed glial infiltration in PD (Hunot and Hirsch, 2003). However it has been also demonstrated that MHC II is upregulated in Parkinson brains, and was not linked to the presence of Lewy‐bodies, indicating, that α‐synuclein might only play a minor role in the recruitment of MHC II positive microglia, and invasion occurs due to the neuronal injury and the associated phagocytosis (Imamura et al, 2003; McGeer et al, 1988). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus in PD itself, α‐synuclein itself might be an antigen used by MHC II during antigen presentation and thus leading to the observed glial infiltration in PD (Hunot and Hirsch, 2003). However it has been also demonstrated that MHC II is upregulated in Parkinson brains, and was not linked to the presence of Lewy‐bodies, indicating, that α‐synuclein might only play a minor role in the recruitment of MHC II positive microglia, and invasion occurs due to the neuronal injury and the associated phagocytosis (Imamura et al, 2003; McGeer et al, 1988). …”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions the central nervous system expresses low levels of MHC II (Shrikant and Benveniste, 1996); however increases in MHC II levels have been documented in a number of pathological states including multiple sclerosis (Hofman et al, 1986) and Alzheimer's disease (Parachikova et al, 2007). Increases in MHC II‐positive cells have long been recognised in human post‐mortem tissue from PD patients (Imamura et al, 2003; McGeer et al, 1988). Also an increase in the number of MHC II‐positive microglia is seen in mice treated with 1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine (MPTP), a drug which induces a PD‐like disease in mice (Kurkowska‐Jastrzebska et al, 1999a, 1999b).…”
Section: Introductionmentioning
confidence: 99%
“…Microglia are present throughout the brain and are higher in the substantia nigra (12% of cells) than in the cortex (only 5%) (Kim et al, 2000;Lawson et al, 1990). In PD patients, the substantia nigra was found to have more than 6-time the number of reactive microglia as compared to the control brains (McGeer et al, 1988a;McGeer et al, 1988b). Microglia activation is involved in the cytotoxicity of neurotoxins such as MPTP, rotenone, substance P, and methamphetamine (Block et al, 2006;Delgado, 2003;Gao et al, 2002;Gao et al, 2003b;Scheller et al, 2005;Thomas et al, 2004;Wu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Resting microglial cells can be activated by Ab in brain, they migrate and surround the region of compact Ab deposits, where they help removing Ab ( [7,65,73,144,155,248]). These data argue in favour of an essential role of microglia cells.…”
Section: Alzheimer's Disease and Neuroinflammationmentioning
confidence: 99%
“…The observation that activated microglia are present at amyloid deposits in human AD and in animal models of this disease suggested that it might play a pathogenic role as a result of their chronic activation, although the presence of cytoplasmic Ab granules in plaque-associated glia and microglia suggest that these cells participate in the clearance of Ab ( [7,42,65,73,125,144,155,180,215,248,254,257,259]). However, this hypothesis is hard to prove using experimental models of this disease in which many pathological features occur, namely amyloid deposition, neurofibrillary tangle formation, inflammation, neuritic and neuronal loss, synaptic and neuronal dysfunction, vascular alterations [197].…”
Section: Animal Models Of Alzheimer's Diseasementioning
confidence: 99%